2014
DOI: 10.1186/1472-6963-14-229
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Québec’s healthcare reforms on the organization of primary healthcare (PHC): a 2003-2010 follow-up

Abstract: BackgroundHealthcare reforms initiated in the early 2000s in Québec involved the implementation of new modes of primary healthcare (PHC) delivery and the creation of Health and Social Services Centers (HSSCs) to support it. The objective of this article is to assess and explain the degree of PHC organizational change achieved following these reforms.MethodsWe conducted two surveys of PHC organizations, in 2005 and 2010, in two regions of the province of Québec, Canada. From the responses to these surveys, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…131 To these outcomes must be added the perennial uncertainties of implementation, especially when changes (such as revising occupational roles) are contentious and may be resisted or renegotiated. 95 As Pineault et al 60 observed in Québec, modifications of structures and resources come first, with new working practices always lagging behind.…”
Section: Perverse or Unforeseen Outcomesmentioning
confidence: 98%
See 4 more Smart Citations
“…131 To these outcomes must be added the perennial uncertainties of implementation, especially when changes (such as revising occupational roles) are contentious and may be resisted or renegotiated. 95 As Pineault et al 60 observed in Québec, modifications of structures and resources come first, with new working practices always lagging behind.…”
Section: Perverse or Unforeseen Outcomesmentioning
confidence: 98%
“…Change in ICIT score was associated with both this evolutionary trend and central reform policies. 60 Decisions from higher authority were the third mechanism for the formation of MCP-like entities. Decreed 'top-down' reform was instrumental and an obvious prerequisite for initiating change in the Québec health-care system.…”
Section: Chaptermentioning
confidence: 99%
See 3 more Smart Citations